Pharmacological Treatment for Obesity in Adults: An Umbrella Review. Issue 7 (July 2020) - Khalil, Hanan; Ellwood, Laura; Lord, Heidi; Fernandez, Ritin
Objective: To synthesize the evidence from systematic reviews of clinical trials investigating the effectiveness of pharmacological therapies approved by the Australian Therapeutic Goods Administration and the US Food and Drug Administration for the management of obesity in adults.Data Sources: A 3-step literature search of the MEDLINE, EMBASE, CINAHL, and PubMed databases was conducted between March and May 2019. The key terms used were obesity, pharmacological therapy, antiobesity agent, antiobesity medication, weight loss, and systematic review.Study Selection and Data Extraction: Systematic reviews that evaluated the effectiveness of pharmacological therapies for the management of obesity in patients with a body mass index of or greater than 25 kg/m 2 .Data Synthesis: Nine systematic reviews involving three pharmacotherapies, liraglutide, orlistat, and naltrexone-bupropion were identified. The results indicate that the pharmacotherapies reduced weight when compared with placebo. Orlistat was effective in significantly reducing fasting blood glucose, HbA1c, total cholesterol, triglycerides, and systolic and diastolic blood pressure. All reviews discussed the presence or risk of gastrointestinal adverse effects including diarrhea, vomiting, and nausea related to orlistat and liraglutide.Relevance to Patient Care and Clinical Practice: This umbrella review compares the efficacy and safety of antiobesity medications for reducing weight and a discussion on their weight loss and metabolic control to guide clinicians when prescribing medications for obesity.Conclusions: All pharmacological therapies included in this review are superior to placebo in reducing weight. Clinicians should consider patient comorbidities and risk of adverse events when recommending medications for weight loss.